2020
DOI: 10.1108/jaoc-03-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Determinants driving Takaful and cooperative insurance financial performance in Saudi Arabia

Abstract: Purpose This paper aims to examine the effect of insurance specific characteristics, corporate governance and risk reporting attributes, Shari’ah board and inflation rate on the financial performance of Takaful and cooperative insurance industries. Design/methodology/approach Based on a dynamic panel generalized method of moment’s system estimation, the author investigates determinants of financial performance as measured by the net premium written, earning ratio and profit margin. Findings Company size, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 35 publications
6
27
1
10
Order By: Relevance
“…Present research contributes to DEA and managerial efficiency by identifying the clear-cut market leader in terms of managerial efficiency. Consistent with recent research on efficiency of insurance companies in KSA (Akhtar Muhammad, 2018;Almulhim, 2019;Benyoussef & Hemrit, 2019;Hemrit, 2020), our findings earmarked the companies that are highly efficient in managerial efficiency. The major take-away from the current study could be summarized as follows.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Present research contributes to DEA and managerial efficiency by identifying the clear-cut market leader in terms of managerial efficiency. Consistent with recent research on efficiency of insurance companies in KSA (Akhtar Muhammad, 2018;Almulhim, 2019;Benyoussef & Hemrit, 2019;Hemrit, 2020), our findings earmarked the companies that are highly efficient in managerial efficiency. The major take-away from the current study could be summarized as follows.…”
Section: Discussionsupporting
confidence: 92%
“…However, in the last decade, researchers have also focused on measurement of efficiency in the insurance sector (Akhtar Muhammad, 2018;Masud, Rana, Mia, & Saifullah, 2019;Al-Amri, 2015;Almulhim, 2019;Barros et al, 2014;Eling & Luhnen, 2010;Hwang & Tong-Liang, 2006;Mandal, 2014;Nourani et al, 2017) as well. Most recent studies in KSA insurance sector (Akhtar Muhammad, 2018;Almulhim, 2019;Benyoussef & Hemrit, 2019;Hemrit, 2020) evaluated the general, pure and technical efficiencies of insurance companies operated in the kingdom. But it seems that managerial efficiencies of insurance firms still need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, total assets (Table 4, models 1 and 2) are negatively and significantly related to the NPE and investment incomes, indicating companies with larger assets underperform the smaller companies. This contradicts the economies of scale, where larger firms are more likely to perform better (Ansah-Adu et al, 2012;Hemrit, 2020). The results are partially consistent with (Akotey et al, 2013), who found that investment income is negatively related to total assets, and they suggested that when the management is not efficient in underwriting and managing the premiums, the assets of firms are financed by the money supposed to be invested.…”
Section: Regression Estimationsupporting
confidence: 74%
“…We use two dependent variables to compare the performance of insurance and Takaful companies. First, the net premium earned is used in the literature to measure the performance, and it indicates the premium earned as the time of policy passes (Hemrit, 2020;Hussein et al, 2014). All premiums paid by the policyholders are part of earned profit if these premiums have not filed claims.…”
Section: Variables Measurements and Modelmentioning
confidence: 99%
“…Well in this Takaful, the funds deposited will still belong to the participant and the company will only manage it. In this case, it is clear that the role and Islamic insurance companies are quite a lot starting from administrators, risk managers, as well as managing funds to be invested (Hemrit, 2020…”
Section: The Management Of the Fundmentioning
confidence: 99%